A Covalent‐Like Feature of Intermolecular Hydrogen Bonding in Energetic Molecules 3, 6‐Dihydrazino‐s‐tetrazine (DHT). Issue 9 (8th August 2021) - Wang, Rui; Wang, Jia; Zhu, Yu; Yu, Famin; Yang, Yanqiang; Wang, Zhigang
Abstract: To explore how intermolecular hydrogen bond (H‐bond) interactions enhance the density and stability of energetic molecular systems, the intermolecular H‐bonding nature of different dimer isomers derived from a new‐generation ecofriendly energetic molecule, 3, 6‐dihydrazino‐s‐tetrazine is studied. First‐principles calculations showed that the critical point of the electron localization function on H‐bonds (H…N) lines increased with the enhancement of the H‐bond strength, confirming that covalent properties of H‐bonds are more important as their strength is stronger. Further energy decomposition analysis indicates that the induced effect accounts for more than 18% of intermolecular interaction attraction terms in planar isomers, reflecting the indispensable covalent‐like feature of H‐bonds in energetic molecular systems. Moreover, molecular orbitals exhibit clear delocalization characteristics penetrating H‐bond regions, which also provide important evidence for covalent‐like features of H‐bonds. These findings provide new insights to further understand and even regulate the insensitivity of energetic materials. Abstract : Intermolecular H‐bonds exhibit covalent‐like features in 3, 6‐dihydrazino‐s‐tetrazine energetic molecules. Particularly, the covalent properties of H‐bonds are more important with the enhancement of their strength. The induced effect accounts for more than 18% of intermolecular interaction attraction terms in planar isomers, reflecting the indispensable covalent‐like feature of H‐bonds. These findings provide new insights how H‐bonding enhance stability of energetic molecules.